2008년 재정사업 모니터링 연구 (산림보호국) - 석현덕 (한국농촌경제연구원, 2008)
We have recognized the importance of various functions of forest: purifying air, reserving water, and providing recreational opportunities. The Korea Forest Service recognizes these demands and responds by way of launching major forest projects. The purpose of this study is ultimately to drive a sustainable forest management by way of verifying problems of the forest projects and providing desirable solutions for the major forest projects. The monitoring project consists of five major fiscal projects: Ecological Forest Establishment, Forest Fire Aviation Control, Erosion Control, Forest Roads Construction, and Pest and Disease Control. Though several problems in each project are revealed, the monitoring results show that each project generally performs well. Most of the revealed problems are being fixed by way of feedback. Policy implications and future proposals for enhancing the performance of projects are also proposed. Researchers: Hyun Deok Seok(Ph.D.), Cheol Su Chang(Ph.D.), Young Dan Kim and Hyeon Geun Kim E-mail address: hdseok@krei.re.kr